The Influence of Flashcard Media on Science Learning Outcomes for Islamic Elementary School Grade - Sehartian, Dea Yunia; Adriyani, Zuanita (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study starts from the researchers’ interest in the use of flashcard media for the elementary school level because seeing the facts in the field that students are only monotonous while in the classroom caused of teacher-centered learning. This research is quantitative research with an experimental approach conducted at MI NU 56 KrajanKulon Kendal with the aim to find out the effect of flashcard media on science learning outcomes for fifth-grade students of MI NU 56 Krajankulon Kendal. The population in this study were all fifth-grade students, totaling 126 students. From this population, the researchers used a simple random sampling technique to take the sample of this study. As a result, the chosen class to be the experimental class is the fifth B grade, consisting of 32 students, and the control class is the fifth A grade, consisting of 32 students. The data used in this research are primary data and secondary data. Primary data was obtained through questionnaires which were shared with fifth-grade students, while the secondary data is in the form of supporting literature on flashcard media and science learning outcomes. The data collection was conducted using multiple-choice tests and documentation. The data analysis technique is descriptive statistics, and the hypothesis test used is the T-test. And the results of the hypothesis test showed that the calculated t value is 4.067 > 1.669 with a significance level of 0.000 with the df = (n-1) of 63; therefore the t table value is at a significant level of 0.05. thus the t count > the t table or 4.067 > 1.669 then it can be stated that H0 is rejected and Ha is accepted. In conclusion, there is an influence between the use of flashcard media on science learning outcomes.